"Placebo Tests" for the Impacts of Air Pollution on Health: The Challenge of Limited Healthcare Infrastructure - Bruna Guidetti; Paula Pereda; Edson R. Severnini (Institute of Labor Economics (IZA), 2021)
When examining the impacts of exposure to air pollution on health outcomes, researchers usually carry out "placebo tests" to provide evidence in support of their identification assumption. In general, this exercise targets health conditions seemingly unrelated to air pollution. In this study, we argue that one should proceed with caution when running such falsification tests. If healthcare infrastructure is limited, when we observe health shocks such as those driven by air pollution, the infrastructure needs to be adjusted to meet the increased demand by canceling or rescheduling elective and non-urgent procedures, for example. As a result, even health conditions seemingly unrelated to air pollution may be indirectly affected by pollution.
Keywords: I15; Q53; Q56; O13; 330; placebo tests; air pollution; healthcare infrastructure; health outcomes; hospitalization for respiratory diseases and other causes